Treating traumatic thoracolumbar spine fractures using minimally invasive percutaneous stabilization plus balloon kyphoplasty: a 102-patient series. (23rd March 2021) - Salle, Henri; Meynard, Alexandre; Auditeau, Emilie; Gantois, Clément; Rouchaud, Aymeric; Mounayer, Charbel; Faure, Patrick; Caire, François
Abstract : Background: There is no consensus on the treatment for spinal injuries resulting in thoracolumbar fractures without neurological impairment. Many trauma centers are opting for open surgery rather than a neurointerventional approach combining posterior percutaneous short fixation (PPSF) plus balloon kyphoplasty (BK). Objective: To assess the safety and efficacy of PPSF+BK and to estimate the expected improvement by clarifying the factors that influence improvement. Methods: We retrospectively reviewed patients who underwent PPSF+BK for the treatment of single traumatic thoracolumbar fractures from 2007 to 2019. Kyphosis, loss of vertebral body height (VBH), clinical and functional outcomes including visual analog scale and Oswestry disability index were assessed. We examined the overall effects in all patients by constructing a linear statistical model, and then examined whether efficacy was dependent on the characteristics of the patients or the fractures. Results: A total of 102 patients were included. No patient experienced neurological worsening or wound infections. The average rates of change were 74.4% (95% CI 72.6% to 76.1%) for kyphosis and 85.5% (95% CI 84.4% to 86.6%) for VBH (both p<0.0001). The kyphosis treatment was more effective on Magerl A3 and B2 fractures than on those classified as A2.3, as well as for fractures with slight posterior wall protrusion on the spinal canal. A higher postoperative visual analog scale score was predictive of poorer outcome at 1 year. Conclusions: This is the largest series reported to date and confirms and validates this surgical treatment. All patients exhibited improved kyphosis and restoration of VBH. We advise opting for this technique rather than open surgery.